PEMANDUAN BAKAT DAN MINAT CABANG OLAHRAGA MELALUI METODE SPORT SEARCH PADA SISWA SMP NEGERI SE KECAMATAN KARANGANYAR KABUPATEN DEMAK TAHUN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of the study : 1 ) To determine the student's interests against those sports, 2 ) To determine the student talent to those sports, 3 ) To determine the suitability of the results between the talents and interests of students towards those sports. The results showed that the factors that best supports students' interest towards the sport is an intrinsic factor ( 71.83 % ) and extrinsic factors ( 61.10 % ) . Judging from the interest that each student has a 44.03 % interest in the sport of football , 25.68 % have an interest in badminton , has a 3.67% interest in the sport of martial arts , has a 5.50 % interest in the outdoor sports , has a 9.17 % interest in the sport of basketball , has a 0.91 % interest in the sport of karate , has a 8.25% interest in the sport of volleyball , has a 1.83 % interest in the sport gymnastics , and 0.91 % have an interest in the sport of table tennis . While the results of the fit between talent and interest in the sport in Secondary Schools as the District Karanganyar Demak amounted to 41.29 % are moderate. In this study it can be concluded that the scouting talent and interest in the sport in Secondary Schools as the District Karanganyar Demak year 2013/2014 in the category of medium.